The Unusual Response of Serotonergic Neurons after CNS Injury: Lack of Axonal Dieback and Enhanced Sprouting within the Inhibitory Environment of the Glial Scar - Hawthorne, Alicia L. (Society for Neuroscience, 2011)
Serotonergic neurons possess an enhanced ability to regenerate or sprout after many types of injury. To understand the mechanisms that underlie their unusual properties, we used a combinatorial approach comparing the behavior of serotonergic and cortical axon tips over time in the same injury environment in vivo and to growth-promoting or growth-inhibitory substrates in vitro. After a thermocoagulatory lesion in the rat frontoparietal cortex, callosal axons become dystrophic and die back. Serotonergic axons, however, persist within the lesion edge. At the third week post-injury, 5-HT+ axons sprout robustly. The lesion environment contains both growth-inhibitory chondroitin sulfate proteoglycans (CSPGs) and growth-promoting laminin. Transgenic mouse serotonergic neurons specifically labeled by enhanced yellow fluorescent protein under control of the Pet-1 promoter/enhancer or cortical neurons were cultured on low amounts of laminin with or without relatively high concentrations of the CSPG aggrecan. Serotonergic neurons extended considerably longer neurites than did cortical neurons on low laminin and exhibited a remarkably more active growth cone on low laminin plus aggrecan during time-lapse imaging than did cortical neurons. Chondroitinase ABC treatment of laminin/CSPG substrates resulted in significantly longer serotonergic but not cortical neurite lengths. This increased ability of serotonergic neurons to robustly grow on high amounts of CSPG may be partially due to significantly higher amounts of growth-associated protein-43 and/or β1 integrin than cortical neurons. Blocking β1 integrin decreased serotonergic and cortical outgrowth on laminin. Determining the mechanism by which serotonergic fibers persist and sprout after lesion could lead to therapeutic strategies for both stroke and spinal cord injury.